Neuro-Development and Psychological Issues in Congenital Heart Defects - Antonio F. Corno (Frontiers Research Topics, 2018)
The advances in the peri-operative management of congenital heart defects have substantially improved the survival of infants over the last few decades, reaching >95% survival in the reports of the international congenital data-base from the European Association of Cardio-Thoracic Surgery and form the Society of Thoracic Surgery (North-America). Nevertheless, the surviving children often experience neurodevelopmental deficits and behavioral, emotional and social issues. These problems often have a profound impact on the quality of life of the growing population of these children at risk and their families.